2020
DOI: 10.3390/toxics8030064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perfluorooctanoic Acid on the Epigenetic and Tight Junction Genes of the Mouse Intestine

Abstract: Perfluorooctanoic acid (PFOA) has been implicated in various toxicities including neurotoxicity, genotoxicity, nephrotoxicity, epigenetic toxicity, immunotoxicity, reproductive toxicity, and hepatotoxicity. However, information on the accumulation of PFOA in the intestine and its toxic effects on intestinal epigenetics and tight junction (TJ) genes is sparse. CD1 mice were dosed with PFOA (1, 5, 10, or 20 mg/kg/day) for 10 days, and its accumulation and induced alterations in the expression of epigenetic and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 88 publications
3
15
0
Order By: Relevance
“…epithelia throughout the body including the blood-brain barrier (Burek et al 2019) and the epididymis (Dubé et al 2010). Notably, a recent study of PFOA exposure in mice reported changes in the expression of tight junction genes in the small intestine, with possible adverse impacts on gut barrier functions (Rashid et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…epithelia throughout the body including the blood-brain barrier (Burek et al 2019) and the epididymis (Dubé et al 2010). Notably, a recent study of PFOA exposure in mice reported changes in the expression of tight junction genes in the small intestine, with possible adverse impacts on gut barrier functions (Rashid et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2010 ). Notably, a recent study of PFOA exposure in mice reported changes in the expression of tight junction genes in the small intestine, with possible adverse impacts on gut barrier functions ( Rashid et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of UC has previously been reported in response to high exposure to PFOA through contaminated drinking water in mid-Ohio, United States (U.S) [7]. This observation is supported by findings from animal studies, where PFOA has been reported to alter the immune response and the barrier function via regulation of various cytokines and tight junction proteins [8].…”
Section: Introductionmentioning
confidence: 55%
“…Contamination of drinking water with high levels of PFOA, one of the most common PFAS, has also been associated with an increased incidence of UC in the state of Ohio, U.S. [7]. A recent study further showed that mice dosed with PFOA during 10 days displayed an altered expression of tight junction genes in the ileum compared to the colon [8]. These observations indicate that PFAS may play a role in the pathophysiology of IBD and potentially act as an environmental trigger.…”
Section: Discussionmentioning
confidence: 99%
“…Ten-eleven translocation (TETs) family of enzymes play a crucial role in the demethylation, by catalyzing the hydroxylation of 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), 5-hmC to 5-formylcytosine (5-fC) and 5-fC to 5-carboxylcytosine (5-caC). Thus, DNA methyltransferases and Ten-eleven translocation enzymes play a coordinating role in modifying the epigenome [ 77 ]. Our results for gene expression analysis for DNMTs and TETs indicated decreased expression of DNMT1 and DNMT3b on exposure to higher doses (200- and 400 μM) of PFOA and PFOS, and increased expression of TET2 on PFOS exposure, and TET3 at higher doses (200- and 400 μM) of PFOA and PFOS.…”
Section: Discussionmentioning
confidence: 99%